A RARE CASE OF AN EXTENSIVE SUBCUTANEOUS NECROSIS IN THE LEFT TEMPORAL REGION CAUSED BY ORANGE OIL INJECTION AND ITS MANAGEMENT - Hayri Ömer Berköz; Bora Edim Akalın; Erol Kozanoğlu; Mehmet Solmaz; Mehmet Yıldıran; Ufuk Emekli (İstanbul Tıp Fakültesi Dergisi)
Orange oil (isoparaffin C11-C15) is a solvent material that dissolves tooth filling materials effectively. A 29-year-old male who had extensive subcutaneous left temporal necrosis after an inadvertent orange oil injection is presented. Due to the injection, an immediate oedema and cellulitis formed in the left buccal, zygomatic, and temporal region. After a prompt drainage and antibiotherapy, the patient’s complaints were resolved. Due to partial temporal muscle necrosis and fibrosis, the interincisal mouth opening (IIO) was 15 millimeters. With a precise physical medicine and rehabilitation regimen, the IIO became 35 millimeters at the postoperative first year